Mekanisme Arbitrase di Badan Arbitrase Nasional Indonesia: Solusi Efektif untuk Penyelesaian Sengketa Bisnis - Aulya, Rizki; Maulana, Intan (Journal of Legal Sustainability, 2024)
The aim of this research is to analyze the role and effectiveness of the Indonesian National Arbitration Board (BANI) in dispute resolution. The method used is a literature study to collect information related to the process and mechanism for dispute resolution through BANI. The analysis was carried out to evaluate the strengths and weaknesses of using BANI as a dispute resolution tool. The research results show that BANI provides an effective platform for parties involved in disputes to resolve disputes peacefully and fairly. The arbitration process through BANI has proven to be fast, efficient and reliable in handling various types of disputes, especially in business and commercial contexts. However, challenges such as costs and compliance with arbitration awards remain a concern. In conclusion, a better understanding of the role and process of dispute resolution through BANI can help parties involved in a dispute to make informed decisions and reach a satisfactory resolution for all parties.